Sudden Slap: Sudden Death - Jakkam, Surendar; Rao, G S R K G Ranga; Prasad, G K V (Journal of Indian Academy of Forensic Medicine, 2015)
A female unconscious patient aged about 72 years brought to the Govt. General Hospital of Rangaraya Medical College, Kakinada, Andhra Pradesh with a history of slap over the cheek. After examination by causality doctors, declared dead. Body was send to the mortuary same hospital. This was the result of a petty quarrel between two persons for theft of mangoes, into which this old lady entered. She got a slap on her cheek. Suddenly she fell down and found dead. Autopsy was conducted on 06/08/2014, in the same hospital’s after receiving all necessary documents from the police people. On examination, there were no external and internal injuries found. With no positive post-mortem findings and presence of history of slap over cheek indicating that it is a case of sudden death due to vaso-vagal shock which occurred by stimulation of baroreceptors situated at the level of angle of mandible.